2008
DOI: 10.1287/moor.1070.0298
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Limits for Processor-Sharing Queues with Impatience

Abstract: Abstract. We investigate a processor sharing queue with renewal arrivals and generally distributed service times. Impatient jobs may abandon the queue, or renege, before completing service. The random time representing a job's patience has a general distribution and may be dependent on its initial service time requirement. A scaling procedure that gives rise to a fluid model with nontrivial yet tractable steady state behavior is presented. This fluid model model captures many essential features of the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…State descriptors of this kind were proposed in Gromoll and Kruk (2007) and Gromoll et al (2008) for processor sharing queues with soft and firm deadlines, respectively. Let…”
Section: Basic Performance Processesmentioning
confidence: 99%
“…State descriptors of this kind were proposed in Gromoll and Kruk (2007) and Gromoll et al (2008) for processor sharing queues with soft and firm deadlines, respectively. Let…”
Section: Basic Performance Processesmentioning
confidence: 99%
“…Puha and Williams [17] and Gromoll [11] established the analogue results for the PS queue. Recent developments include the analysis of PS queues with impatience [13], [14].…”
Section: Literaturementioning
confidence: 99%
“…It is studied in Gromoll et al [8] and shown to have a unique solution that is bounded away from zero outside t = 0, see Corollary 3.8. So the norm z(·) 1 is unique.…”
Section: Theorem 1 For Any Initial State Z(0) a Fms Exists And Is Umentioning
confidence: 99%
“…To establish convergence of fluid limits to the invariant point, we use an equivalent description of fluid limits, which is a generalisation of the approximating equation suggested by Gromoll et al [8] for a single-stage-service PS queue. We also discuss the method of of Lyapunov functions since the model treated in this paper is an instant of a more general open problem: no Lyapunov function is known for a PS-queue with routing and impatience.…”
Section: Introductionmentioning
confidence: 99%